2015
DOI: 10.1017/ppr.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Surveys of Stonehenge and its Environs, 2009–2013: Part 2 – the Stones

Abstract: Non-invasive survey in the Stonehenge ‘Triangle’, Amesbury, Wiltshire, has highlighted a number of features that have a significant bearing on the interpretation of the site. Geophysical anomalies may signal the position of buried stones adding to the possibility of former stone arrangements, while laser scanning has provided detail on the manner in which the stones have been dressed; some subsequently carved with axe and dagger symbols. The probability that a lintelled bluestone trilithon formed an entrance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Several authorities have suggested that the sarsens were sourced from the area of Stonehenge or somewhere closely adjacent (see below). Darvill et al (2012, 1029) have recently suggested that some stone was probably present on site at the outset; notably the massive cone-shaped Heelstone as it has been considered to have been extremely difficult to move (Johnson 2008, 121), an observation supported by measurements taken from the laser scan data which demonstrates that it is the heaviest stone on site (Abbott & Anderson Whymark 2012; Field et al forthcoming).…”
Section: Periglacial Geography and Holocene Land Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Several authorities have suggested that the sarsens were sourced from the area of Stonehenge or somewhere closely adjacent (see below). Darvill et al (2012, 1029) have recently suggested that some stone was probably present on site at the outset; notably the massive cone-shaped Heelstone as it has been considered to have been extremely difficult to move (Johnson 2008, 121), an observation supported by measurements taken from the laser scan data which demonstrates that it is the heaviest stone on site (Abbott & Anderson Whymark 2012; Field et al forthcoming).…”
Section: Periglacial Geography and Holocene Land Surfacementioning
confidence: 99%
“…the land in the angle of the A303 and A344 roads limited by the north–south Larkhill by-way in the west) and, in particular, to introduce the use of ground penetrating radar (GPR; Linford et al 2012). Additionally, both the ground surface and stones themselves were recorded by laser scanning and in the latter case this was supplemented by photogrammetric recording of the upper surfaces of the lintels and freestanding uprights; the stones were thus recorded in unprecedented detail (<0.5 mm resolution) and will be considered separately in part 2 of this report (Field et al forthcoming).
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…1). Moreover, constructional features relating to the method for fitting the stones together, as revealed by field examination and photogrammetric survey, provide evidence of an intention to form a compete circuit (Field et al 2015: 135). As such, it must be concluded that the missing sarsen uprights and lintels were robbed in antiquity.…”
Section: Building Time Into the Fabric Of Stonehengementioning
confidence: 99%
“…The surviving stones of the bluestone oval at the centre of Stonehenge are considerably longer than this, averaging 2.2 m. The stones of the bluestone circle however are somewhat shorteraveraging 1.4 m with less complete examples, which could conceivably have functioned as lintels. Field et al 2015 note that four bluestones (67, 69, 70, and 72) bear scars from the removal of tenons, while stones 150 and 36 are lintels re-used as uprights.…”
Section: Bob Davis Et Al Rti Investigation Of Engraved Chalk Plaquesmentioning
confidence: 99%